Licitações e editais de empreendimentos públicos de construção e sua influência no processo de projeto - Zanferdini, André Saretta (2011)
The delay in the conclusion of the public construction projects, that are frequently paralyzed, as well as the foreseen cost rise, may highlight the existence of recurrent technical, financial, political, administrative or judicial problems, which were originated even before hiring a firm. Therefore, this paper aims to analyze how the bidding and engineering work contracts refereeing legislation, within the Powers of Union, of States and Municipal district, contributes so that the solutions taken from designs do not get fully attended during the process of public construction ventures. Such a purpose, which initially required additional knowledge on public construction projects and design process, which was achieved with the execution of the literature review and the case studies, that in turn involved three public contracting companies and three contracted firms, as a way to get different perceptions of the same process. The evidence obtained from the contract bidding analysis, properly validated with answers from series of questions applied to contracting party and contracted, along with the literature review provided the conclusion of this work, as well as the creation of a proposal that aims to reduce the problems related to the accomplishment of the solutions taken from designs of public construction projects.